Constructing physician-assisted dying: the politics of evidence from permissive jurisdictions in Carter v. Canada. (2nd January 2017) - Karsoho, Hadi; Wright, David Kenneth; Macdonald, Mary Ellen; Fishman, Jennifer R.
Abstract: Since the 1990s, there has been a growing global movement to legalise the controversial practice of physician-assisted dying (PAD). In the last twenty years, 13 jurisdictions have decriminalised or legalised PAD which, in turn, have produced new knowledge on the practice. The recent case of Carter v. Canada, which decriminalised PAD in Canada in 2015, provides us with an empirical opportunity to investigate how actors deployed and interpreted this new knowledge. We found that actors used expert evidence from permissive jurisdictions to construct different meanings of PAD as a legalised medical practice. The opponents constructed PAD as a practice accessed by patients who were suicidal, performed by uncaring physicians unskilled in end-of-life care, and loosely regulated through a fallible regime. The proponents used the evidence to construct PAD as a practice borne out of a patient's rational choice, performed by caring physicians within an environment where end-of-life care had improved since legalisation, and tightly regulated through a regime where participants function as sentries overseeing each other's actions. In the final analysis, we argue that the proponents' success in this case contributed to the production and reproduction of a specific cultural script that renders PAD culturally appropriate.